ANALISIS PENGARUH PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DIBURSA EFEK INDONESIA (BEI) - Marsanda Maulana P; Anisafitri Anisafitri (CV. Adiba Aisha Amira, 2026)
This study aims to analyze the effect of profitability on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX). Profitability is measured using Return on Assets (ROA), while firm value is measured using the Price to Book Value (PBV). This research uses secondary data in the form of annual financial statements of manufacturing companies for the 2022–2023 period. The research sample was obtained using purposive sampling, consisting of 30 companies. The data analysis methods employed are descriptive statistics and simple linear regression. The results indicate that profitability has a positive and significant effect on firm value. These findings suggest that the higher the level of a company's profitability, the higher its value in the eyes of investors